Constitutional revolutions : pragmatism and the role of judicial review in American constitutionalism - Lipkin, Robert Justin, 1943- (E-Duke books scholarly collection., 2000)
Rethinks constitutional jurisprudence from a postmodern perspective, attempting to integrate a Kuhnian approach to intellectual transformations with a Rawlsian pragmatic approach to decision making.